1997
DOI: 10.1177/0011128797043001004
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Educational Attainment on the Attitudes and Job Performance of Correctional Officers

Abstract: Some prison managers assume that recruitment of correctional officers with postsecondary educational credentials promotes job satisfaction and offender rehabilitation. This assumption was tested using a sample of 218 officers. Results supported earlier findings that postsecondary education correlates with endorsement of rehabilitation and job dissatisfaction. However, university graduates were not more willing than less-educated officers to engage in offender treatment and there were no apparent effects of edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 26 publications
2
85
1
Order By: Relevance
“…While correctional administrators' efforts to raise minimum educational requirements in recent decades have been well documented (Cullen et al 1989;Jurik and Musheno 1986), there have been few examples whereas administrators have strategically delimited what types of higher education are preferred (Robinson et al 1997). The relationship between higher education levels and job satisfaction have primarily identified negative relationships (Jurik and Musheno 1986;Cullen et al 1989;Robinson et al 1997).…”
Section: Stress For Probation and Parole Officersmentioning
confidence: 99%
“…While correctional administrators' efforts to raise minimum educational requirements in recent decades have been well documented (Cullen et al 1989;Jurik and Musheno 1986), there have been few examples whereas administrators have strategically delimited what types of higher education are preferred (Robinson et al 1997). The relationship between higher education levels and job satisfaction have primarily identified negative relationships (Jurik and Musheno 1986;Cullen et al 1989;Robinson et al 1997).…”
Section: Stress For Probation and Parole Officersmentioning
confidence: 99%
“…Studies of correctional officers' attitudes about their job, offenders, or rehabilitation philosophy have highlighted differences in attitudes based on an officer's age, education, gender, or years of service (Farkas 1999;Hemmens and Stohr 2001;Latessa and Allen 1999;Maahs and Pratt 2001;Robinson et al 1997;Zupan 1986). Robinson et al (1997) examined 213 corrections officers and found that officers who had higher levels of education were more likely to possess favorable attitudes towards rehabilitation.…”
Section: Community Corrections Officers' Perceptionsmentioning
confidence: 99%
“…Robinson et al (1997) examined 213 corrections officers and found that officers who had higher levels of education were more likely to possess favorable attitudes towards rehabilitation. In an examination of 125 corrections officers, Farkas (1999) found that older officers favored rehabilitation more than younger officers and that female officers exhibited more of a counseling role with offenders.…”
Section: Community Corrections Officers' Perceptionsmentioning
confidence: 99%
“…Still other researchers have suggested that too much education could reduce job satisfaction (Dantzker 1998;Mineard 2006;Robinson et al 1997). Generally speaking, findings from this branch of research indicates that the higher the education, the lower the job satisfaction.…”
Section: Introductionmentioning
confidence: 88%